Spatial dominants of Alexander Green's novelistic world - Белогорская, Людмила Вячеславовна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The article investigates the artistic space of novels by Alexander Grin. It is shown that the previous extravaganza "Scarlet Sails" - is a programm creation of the writer which sets the key spatial dominans of the whole body of Green's novels. The main focus is made on the castle toposes (rich house) and the garden, which are reflected in all the subsequent novels of the author, and in the two of them were built up to the level of the sacred narrative center. The topos of the forest path and the restaurant/inn space which were built up in the last novel "The road into nowhere" are also studied in the way of opposition to the extravaganza "The scarlet sails" inn/restaurant.